Smoking interferes with the prognosis of dental implant treatment: a systematic review and meta-analysis - Frank Peter Strietzel (Blackwell Synergy, 2007)
Aim: This systematic literature review was performed to investigate if smoking interferes with the prognosis of implants with and without accompanying augmentation procedures compared with non-smokers. Methods: A systematic electronic and handsearch (articles published between 1989 and 2005; English and German language; search terms ‘‘dental or oral implants and smoking’’; ‘‘dental or oral implants and tobacco’’) was performed to identify publications providing numbers of failed implants, related to the numbers of smokers and non-smokers for meta-analysis. Publications providing statistically examined data of implant failures or biologic complications among smokers compared with nonsmokers were included for systematic review. Results: Of 139 publications identified, 29 were considered for meta-analysis and 35 for systematic review. Meta-analysis revealed a significantly enhanced risk for implant failure among smokers [implant-related odds ratio (OR) 2.25, confidence interval (CI95%) 1.96–2.59; patient-related OR 2.64; CI95% 1.70–4.09] compared with nonsmokers, and for smokers receiving implants with accompanying augmentation procedures (OR 3.61; CI95% 2.26–5.77, implant related). The systematic review indicated significantly enhanced risks of biologic complications among smokers. Five studies revealed no significant impact of smoking on prognosis of implants with particle-blasted, acid-etched or anodic oxidized surfaces. Conclusion: Smoking is a significant risk factor for dental implant therapy and augmentation procedures accompanying implantations.